Volume 1: Processing 2013
DOI: 10.1115/msec2013-1251
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of High Performance Polymer Nanocomposite Using Carbon Nanotubes as Fillers

Abstract: In this work, the chemical vapour deposition (CVD) method is used for the production of carbon nanotubes (CNTs). The catalyst, Fe/MgO, was prepared through sonication technique. It was heated to 600 °C for 6 hours and this was used as the template for growing the CNTs using acetylene as carbon precursor. The deposited CNTs were separated by acid treatment followed by air oxidation. The purified CNTs were examined by scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The discontinuous process consists of two pairs of pressing dies ( Figure 7b); one pair of dies is for corrugation and the other for straightening. Different corrugating die surface profiles that have been reported in the literature include; Vgroove, Flat-groove and Semi-circular die [65][66] [67]. Sketches of these dies are presented in Figure 8.…”
Section: Repetitive Corrugation and Straightening (Rcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The discontinuous process consists of two pairs of pressing dies ( Figure 7b); one pair of dies is for corrugation and the other for straightening. Different corrugating die surface profiles that have been reported in the literature include; Vgroove, Flat-groove and Semi-circular die [65][66] [67]. Sketches of these dies are presented in Figure 8.…”
Section: Repetitive Corrugation and Straightening (Rcs)mentioning
confidence: 99%
“…Thangapandian et al [65] experimented on the effects of semicircular (r =5mm), flat-groove (x=5 mm) and V-groove (x =10 mm: refer to equations 8 and 9) dies on tensile, ductility, hardness and microstructure properties of GP processed Al-Mg alloy sheets, 3mm thick. Results showed that; a semicircular die withstood 15 passes (highest number) without cracking.…”
Section: Effect Of Die Profile On Properties Of Rcs Processed Samplesmentioning
confidence: 99%